2012
DOI: 10.1097/meg.0b013e32834dda64
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of survival and quality of life of hepatectomy and thrombectomy using total hepatic vascular exclusion and chemotherapy alone in patients with hepatocellular carcinoma and tumor thrombi in the inferior vena cava and hepatic vein

Abstract: Hepatectomy and thrombectomy using the total hepatic vascular exclusion, is a viable surgical management for patients with HCC and PVTT, and is associated with longer overall survival and recurrence-free survival and better QoL than chemotherapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…The use of hepatic vascular exclusion may be related to advanced tumour stage, radicality of surgery and increased potential for postoperative complications, as its use can be associated with significant haemodynamic instability. The authors have used this approach in difficult procedures, but normally prefer to apply intrahepatic ligation and division of the major hepatic veins during parenchymal dissection in combination with inflow occlusion by means of an intermittent Pringle manoeuvre.…”
Section: Discussionmentioning
confidence: 99%
“…The use of hepatic vascular exclusion may be related to advanced tumour stage, radicality of surgery and increased potential for postoperative complications, as its use can be associated with significant haemodynamic instability. The authors have used this approach in difficult procedures, but normally prefer to apply intrahepatic ligation and division of the major hepatic veins during parenchymal dissection in combination with inflow occlusion by means of an intermittent Pringle manoeuvre.…”
Section: Discussionmentioning
confidence: 99%
“…Annual transition probabilities, presented in Figure and Table , were taken from published literature . After completion of treatment, patients who were treated at METAVIR fibrosis score F0–F2 and who achieved SVR were assumed to maintain SVR and to experience no further disease progression until their death.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with a successful liver transplant remained in the post‐liver transplant health state until their death. Probabilities of HCV‐related death were taken from published literature on liver‐related mortality for the DCC, HCC and post‐liver transplant health states. For non‐HCV‐related causes of death, mortality was based on US general population probabilities by age …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical resection alone can provide long-term survival only in some HCC patients with HVTT [5, 6, 17]. Clinical trials of hepatic resection combined with chemotherapy, including HAIC, have been reported to improve the survival rate of HCC patients with macrovascular invasion [2426].…”
Section: Discussionmentioning
confidence: 99%